Research on the Influence of Surface Roughness on the Flow Field in the Cascade - Wang, Yanhua; Dai, Jun; Zhou, Shaowei; Wang, Meng; Wang, Zhongyi (Frontiers in Energy Research, 2022)
Fouling, corrosion, and icing are common causes of increased compressor blade roughness due to special operating conditions and natural environment. Roughness increase would influence on flow field, especially in supersonic compressor cascades where incident waves can interact with reflected shock waves. Studies have shown that the boundary layer condition of the blade varies with wall roughness, which affects both the incident shock wave and the reflected shock wave. In order to study the effect of the distribution of roughness, the flow field under different roughness settings is simulated. The results show that flow loss is reduced with increasing roughness at the incidence point of an incident wave and the trailing edge of the suction side.